Entrepreneurship : Morris Sport Center / Noorhidayah Ahmad ... [et al.] - Ahmad, Noorhidayah; Abidi, Nur Adeliah; Mohd Ramli, Mohd Tajul Ariff; Aris, Mohd Zafuan; Khamis, Amy Nadia Khalida (2008)
Our company name is MORRIS SPORT CENTER CORPORATION. Our company will run a sport centre. It’s includes indoor activities such Futsal, Badminton, and Gymnasium. We also provide a cafeteria at our premise for the customer. For our cafeteria, we give to a tender to manage. Rent for the cafeteria will cost RM 1000 in month.